Moult cycle and growth of the crab Halicarcinus planatus (Brachyura, Hymenosomatidae) in the Beagle Channel, southern tip of South America - Diez, Mariano Javier; Lovrich, Gustavo Alejandro (Helgoland Marine Research)
The crab Halicarcinus planatus is the only hymenosomatid crab that inhabits the southern tip of South America and is the only decapod species that reproduces twice a year in the Beagle Channel. In this article, we study the moult cycle in the field (moult frequency, analysis of size frequency distribution) and linked it with growth studied in the laboratory (absolute and percent growth increment, Hiatt function). Hiatt functions were similar for males and females. Moult frequency was seasonal: in early austral spring and in austral summer. In females, the pubertal moult is the terminal moult, whereas males continue moulting after attaining the size of morphometric maturity. Moult increment was highly variable. The relationship between absolute moult increment and crab size was described by a quadratic function. Percent growth increment decreased with size and relationships were different for each sex: linear for females and quadratic for males. Seven and eight modal groups explained the size frequency distributions for females and males from the field, respectively, and revealed the existence of two cohorts of recruits per year. Further modal analysis was mainly hampered by the high variability of size increment that could make any moulting individual fall in its own or one of two following modal groups. The antagonism between growth and reproduction was evident in small males. We hypothesize that the terminal pubertal moult is an advantageous feature that allows females to maximize their investment in reproduction after their terminal moult, which allows this species to have two spawnings per year. Fil: Diez, Mariano Javier. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Lovrich, Gustavo Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina